Pembelajaran Ict Menggunakan Program â€œVectorian Giottoâ€ - Puspitasari, Ika (Prodi Pendidikan Agama Islam - Fakultas Agama Islam ( FAI ), 2019)
AbstractEducation in Indonesia grows in line with the development of Science and Technology. Problems that often arise are influenced by the increasing ability of students, thesituation and environmental conditions, the influence of information and culture, and thedevelopment of science and technology. Purpose of this research explained ICT (InformationCommunication and Technology)Â learning by using the program of â€œvectorian giottoâ€. TheICT LearningÂ can be used to facilitate the cooperation between educators and students.Information and Communication Technology (ICT) can be used as learning media to conveyinformation or teaching materials. As a teacher, it is now required to be able to createinnovative, creative and fun learning media. The â€œvectorian giottoâ€ program is a vector-basedanimation program whose making animation is based the timeline. It serves to provide theobject change points that are writing, images, videos, sounds, etc are from the first changepoint (keyframe) to the point of change next (second keyframe). In the ICT learning courseusing the â€œvectorian giottoâ€Â program, the student is demanded to make innovative andcreative learning media. This program is complete enough to create an illustrative animationin making learning media, users can enter writing, images, videos, or sounds into thisprogram designed as an animation, so that many objects can be compiled through thisprogram used as learning animations.Keywords: ICT, Learning, Program of Vectorian Giottoâ€